Estudio de factibilidad para la creación de una empresa productora y comercializadora de velas aromáticas a base de aceite de cocina reciclado en el municipio de sahagún córdoba año 2019 (2019)
Company: Aromas LK Location: Carrera 11 # 10-80 Barrio Centro. Sahagun-Cordoba Business opportunity: Elaboration of aromatic candles based on recycled cooking oil. Competitors: Beatriz varieties, Joche Cacharrería, Sunflowers, Aromatek. Service: Sale of aromatic candles. Price: The value is $ 11,500 pesos per unit. Investment budget: The fixed investment is $ 111,456,012 million pesos Profitability: The IRR of the business plan is 100%.